Global economics and marketing of citrus products - Spreen, Thomas H.; Gao, Zhifeng; Fernandes, Waldir [UNESP]; Zansler, Marisa L. (Elsevier, 2020)
An overview of the world market for citrus products from an economic, production, and marketing perspective is provided. To conduct an economic analysis of any fruit, it is important to distinguish between fresh and processed utilization. In the case of citrus, there is a degree of regional specialization regarding fresh versus processed citrus products. In this chapter, special attention is given to the largest citrus producing countries: China, Brazil, and the United States. The chapter is divided into the four classes of citrus fruits: sweet oranges, mandarins, grapefruit/pummelos, and lemons/limes. Trade agreements that affect commerce in both fresh and processed citrus products are also reviewed. Efforts to promote the consumption of citrus productions are discussed.
Keywords: Economics; Marketing; Prices; Pricing; Production; Trade